Optimism, pessimism and life satisfaction: An empirical investigation - Alan T. Piper (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This empirical investigation into life satisfaction, using nationally representative German panel data, finds a substantial association with an individual's thoughts about the future, whether they are optimistic or pessimistic about it. Furthermore, including individuals' optimism and pessimism about the future substantially increases the explanatory power of standard life satisfaction models. The thoughts that individuals have about the future contribute substantially to their current life satisfaction. In particular, the reduction in life satisfaction experienced by individuals who report being pessimistic is greater than that for well-understood negative events like unemployment. These effects are attenuated but remain substantial after controlling for individual fixed effects, statistically matching on observable variables between optimistic and pessimistic individuals, and addressing the potential endogeneity of optimism and pessimism to life satisfaction. Moreover, these effects are robust to controlling for future life events that may be anticipated.
Keywords: C23; D84; I31; 330; life satisfaction; subjective well-being; mental health; entropy balancing; GMM; dynamics; endogeneity; SOEP